Survey of United States Congressional Candidates, 1976 ([Verlag nicht ermittelbar], 1984)
This data collection contains the results of a survey of the candidates who ran for United States Senate and the United States House of Representatives in 1976. By surveying such candidates, the Federal Election Commission (FEC) was attempting to collect systematically the views of those directly affected and regulated by the Federal Election Campaign Act (FECA) as it was amended in 1974 and 1976. Those amendments called for significant changes in the rules for campaign contributions and expenditures, restrictions on independent expenditures and in-kind contributions, and public disclosure of all federal campaign activity. The survey was conducted by Decision Making Information of Santa Ana, California, and Hart Research Commission in the first two months of 1976. In all, 850 respondents (candidates, campaign managers, and other campaign representatives) were interviewed by mail or in person. The survey questions focused on seven major topics: (1) actual characteristics of the campaigns and the candidates covered by the survey, (2) experiences during the 1976 election, (3) finances in 1976, (4) impact of the FECA on campaign organization, (5) the role played by the Federal Election Commission (FEC) as an information source for, and regulator of, campaigns, (6) which items dealt with by the FECA were favored or opposed by candidates and campaign managers who participated in the 1976 election, and (7) the respondent's overall feelings about what should be done in the future.